RECENT EVALUATION OF RISING TEMPERATURE AND OIL PALM EXTENSION TO HIGHER ELEVATION IN NORTH SUMATRA(EVALUASI TERKINI KENAIKAN SUHU DAN PERLUASAN TANAMAN KELAPA SAWIT KE DATARAN TINGGI DI SUMATERA UTARA) - Nuzul Hijri Darlan; Hasril Hasan Siregar; Eka Listia; Edy Sigit Sutarta (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2009)
Implication of climate change on oil palm plantation in Indonesia generally not much known, which could be a threat that needs attention, or maybe an opportunity. Climate change could cause the rainy season more wet and dry season drier. At other side, climate change also caused the temperature increased, which could make an extension of oil palm plantation in higher altitude become possible. Nowadays, total area of oil palm plantation in high altitude in north Sumatera was 4.725 hectares. This paper describes recent evaluation of climate change in North Sumatera province and its relation with oil palm extension and the response of oil palm productivity in higher altitude.